A Review of Bioactive Metabolites from Endophytic Fungi: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
High potential for medicinal substances such as anticancer, antioxidant, antibacterial, antidiabetic and industrial enzymes are endophytic fungus The presence of novel illnesses, infections, resistance to drugs and imbalances in ecosystems is now a major problem for human beings. The possible sources for novel treatments were here endophytes. Endophytes are regarded as a bioprospect treasure and help to overcome numerous difficulties in many ways. Most possible microorganisms, which are a reservoir of mostly untapped bioactive compounds, have been identified among the different endophytic bacteria. For their bioactive substances, we must look for endophytes.